Does functional strength training program improve ice speed and agility in young elite ice hockey players? Functional strength training’s impact on hockey performance - Bieniec, Anna; Grabara, Małgorzata (Frontiers in Physiology, 2025)
PurposeThe aim of this study was to investigate the effects of a functional strength training (FST) program on ice speed and agility in young elite male ice hockey players.MethodsForty-three ice hockey players, aged 15–18 years participated in the study. The athletes were randomly assigned to either a functional strength training group (FSTG), which completed an additional FST program consisting of two 60-min training sessions per week, or a control group (CG), which participated in other team games and swimming sessions, each lasting 60 min. Ice skating speed was assessed using the professional Smart Speed measurement system in forward and backward skating tests over 5, 15, and 30 m, as well as in an agility test.ResultsThe intervention elicited significant performance improvements in ice skating speed and agility in the FSTG compared to the CG. Significant time × group interactions were observed in the 5-m (p = 0.041, ηp2 = 0.098), 15-m (p = 0.047, ηp2 = 0.093), and 30-m (p = 0.011, ηp2 = 0.149) forward skating tests, highlighting differential responses between groups. Post hoc analysis confirmed significant improvements in the FSTG, particularly in the 15-m and 30-m tests, where post-test results were superior to those of the CG. No significant effects were found for the backward skating tests. Regarding agility, a significant main effect of time (p = 0.023, ηp2 = 0.12) and group (p = 0.001, ηp2 = 0.226) was detected. In the full speed test, only a group effect (p = 0.026, ηp2 = 0.116) was observed, with no significant time × group interaction or time effects.ConclusionThese results underscore the effectiveness of FST in enhancing forward skating speed and agility.